HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN PAYUDARA DENGAN KELANCARAN PENGELUARAN ASI DI PUSKESMAS PAKUE KECAMATAN PAKUE KABUPATEN KOLAKA UTARA - astri yuliandini; Desi Anggeriani (Stikes Graha Edukasi Makassar, 2022)
Objective: The purpose of this study was to examine the relationship between postpartum mother's knowledge about breast care and the smooth production of breast milk at the Pakue Public Health Center. Methods: this study uses a quantitative approach with a Cross Sectional Study, which is a type of research that emphasizes the measurement/observation of data on independent and dependent variables at one time. The sample size in this study was 30 people who matched the inclusion criteria. Data collection was done by using a questionnaire. Results: The results showed that of the 30 people who were used as samples, 20 people (66.7%). Those who experienced the smoothness of ASI were 19 people (63.3%). The relationship between postpartum mother's knowledge about breast care and the smooth flow of breast milk at the Pakue Public Health Center (p = 0.007). Conclusion: the conclusion of this study is that there is a relationship between postpartum mother's knowledge about breast care and the smooth flow of breast milk. Suggestion: the results of this study can be used as the development of science, especially about breast care to understand the technique and how to do it so that the mother can do it according to the stages